The Pendulum of Power: Tracing Turkey’s Democratic Evolution and Authoritarian Drift - Gabbay, Shaul M. (European Journal of Applied Sciences, 2024)
This paper analyzes Turkey’s historical journey through the evolution of democracy and human rights from the creation of the current Republic, through the current notable drift into authoritarianism under the ruling Justice and Development Party (AKP). By examining Turkey’s democratic development from its original one-party rule at its inception in 1923, to its expansion in a multi-party system in 1946, through a series of military coups, and finally the influence of the European Union accession negotiations, the unreliable outcome of its unsteady embrace of democracy becomes visible. What we are left to grapple with is the veracity of Turkey’s commitment to democracy. As the world stands witness to an ongoing and significant reversal of democratic reforms including increased censorship, suppression of dissent, and erosion of institutional checks and balances, the question arises of how to support Turkey in its return to a country supportive of human rights and freedoms. This paper concludes by addressing the critical factors needed to restore a decisive implementation of democratic resilience.